Coordination-assisted, transition-metal-catalyzed enantioselective desymmetric C–H functionalization. Issue 5 (19th January 2022) - Yu, Xin; Zhang, Zhuo-Zhuo; Niu, Jun-Long; Shi, Bing-Feng
Abstract : Recent advances in transition-metal-catalyzed enantioselective desymmetric C–H functionalization are summarized. Abstract : Transition-metal-catalyzed asymmetric C–H functionalization has gradually emerged as a powerful tool for the creation of structural and chiral complexity in an atom- and step-economical fashion. The nature of this strategy provides a variety of methodologies to overcome the limitation of enantioselective desymmetrization caused by the synthesis of preformed multifunctional symmetric substrates. This review aims to summarise recent advances in transition-metal-catalyzed enantioselective desymmetric C–H functionalization reactions via coordination-assisted metal insertion, covering the literature from 2008 to June 2021. The mechanistic pathway and the modes of stereocontrol are discussed where appropriate.